Color models and their applications in color inspection and farm produce grading - ZHOU Shui-qin; YING Yi-bin (浙江大学学报. 农业与生命科学版, 2003)
The machine vision technology has a encouraging prospect in its application to color inspection and farm produce grading. Several color models and their applications in detecting surface defect, color and maturity of farm produce are introduced in this paper.